WHOIS running the Internet : protocol, policy, and privacy - Bruen,Garth O (2015)
"This book provides a comprehensive overview of WHOIS. The text begins with an introduction to WHOIS and an in-depth coverage of its forty-year history. Afterwards it examines how to use WHOIS and how WHOIS fits in the overall structure of the Domain Name System (DNS). Other technical topics covered include WHOIS query code and WHOIS server details. The book also discusses current policy developments and implementations, reviews critical policy documents, and explains how they will affect the future of the Internet and WHOIS"--
Keywords: WHOIS (Computer network protocol); Internet domain names -- Government policy; Computers; Information Technology